### Related

##### sin

f(x):=2*(sin(2*x)+3)-...

f(3*3.141516/2);

Calculate

##### sin-tan-trigreduce

x+3*tan(x)/4*sin(x), ...

Calculate

##### sin-subst-taylor

f:taylor(sin(%pi/6+x));

f1:subst(x=%pi/24,f);

Calculate

##### sin-trigsimp

trigsimp(sin(x)^2);

Calculate

eq1: sin (2);

eq1;

Calculate

##### sin-solve

eq2:sin(x)+3=y;

solve([eq2],[x,y]);

Calculate

##### sin

f(x,y):=(10*(sin(x)+s...

Calculate

##### sin-taylor

taylor(sin(x),x,0,8);

Calculate

a: sin(%pi/5);

Calculate

##### sin-solve-sqrt

solve(sin(x) =sqrt(3)...

Calculate

### sin

Run Example
```(%i1)plot2d(sin(x)+1, [x,0,6],[y,-2,2]);
plot```
Run Example
```derivabbrev:true ;
(%o1)                                true
(%i2) mainvar: t;
(%o2)                                  t
(%i3) x(t):= r(t)*sin(theta(t));
(%o3)                     x(t) := r(t) sin(theta(t))
(%i4) y(t):=r(t)*cos(theta(t));
(%o4)                     y(t) := r(t) cos(theta(t))
(%i5) xdot(t):= diff(x(t), t, 1);
(%o5)                     xdot(t) := diff(x(t), t, 1)
(%i6) ydot(t):= diff(y(t), t, 1);
(%o6)                     ydot(t) := diff(y(t), t, 1)
(%i7) xdotdot(t):= diff(xdot(t), t, 1);
(%o7)                  xdotdot(t) := diff(xdot(t), t, 1)
(%i8) ydotdot(t):= diff(ydot(t), t, 1);
(%o8)                  ydotdot(t) := diff(ydot(t), t, 1)
(%o9)                 thetadot(t) := diff(theta(t), t, 1)
(%i11) Assumption1: xdotdot(t)=0;
2
(%o11) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 r(t)  cos(theta(t)) theta(t)  + r(t)    sin(theta(t)) = 0
t                       t       t t
(%i12) solve(Assumption1, r(t));
sin(theta(t)) r(t)    + 2 cos(theta(t)) theta(t)  r(t)
t t                           t     t
(%o12) [r(t) = - -------------------------------------------------------]
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i13) Assumption2: ydotdot(t)=0;
2
(%o13) - r(t) sin(theta(t)) theta(t)    - r(t) cos(theta(t)) (theta(t) )
t t                               t
- 2 r(t)  sin(theta(t)) theta(t)  + r(t)    cos(theta(t)) = 0
t                       t       t t
(%i14) E1_1: subst(rdot(t), diff(r(t), t, 1), Assumption1);
2
(%o14) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 rdot(t) cos(theta(t)) theta(t)  + r(t)    sin(theta(t)) = 0
t       t t
(%i15) E1_2: subst(rdotdot(t), diff(diff(r(t), t, 1),t,1), E1_1);
2
(%o15) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t)) = 0
t
(%i16) E1_3: subst(rr(t), r(t), E1_2);
2
(%o16) rr(t) cos(theta(t)) theta(t)    - rr(t) sin(theta(t)) (theta(t) )
t t                                t
+ 2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t)) = 0
t
(%i17) E1_4: solve(E1_3, rr(t));
2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t))
t
(%o17) [rr(t) = - ------------------------------------------------------------]
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i18) E1_5: subst(r(t), rr(t), E1_4[1]);
2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t))
t
(%o18) r(t) = - ------------------------------------------------------------
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i19) ```
Run Example
```f: x^3 * %e^(k*x) * sin(w*x);
3   k x
(%o1)                          x  %e    sin(w x)
(%i2) int (f,x);
3   k x
(%o2)                      int(x  %e    sin(w x), x)
(%i3) ```

Help for Sin